Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
=>\(x\times4+x\times8+x\times2=1,4\)
\(\Rightarrow x\times\left(4+8+2\right)=1,4\)
\(\Rightarrow x\times14=1,4\)
\(\Rightarrow x=1,4\div14\)
\(\Rightarrow x=0,1\)
x : 0,25 + x : 0,125 + x : 0,5 = 1,4
x : ( 0,25 + 0,125 + 0,5 ) = 1,4
x : 0,875 = 1,4
x = 1,4 x 0,875
x = 1,225
Chúc bn hc tốt <3
b, \(x\)x \(\frac{1}{4}\)+ \(x\)x \(\frac{1}{5}\)+ \(x\)x 2 = 19,6
\(x\)x (\(\frac{1}{4}+\frac{1}{5}+2\)) = 19,6
\(x\)x\(\frac{49}{20}\)= 19,6
\(x\) = \(19,6:\frac{49}{20}\)
\(x=8\)
( 1.1 x 1.2 x 1.3 x 1.4 x 1.5 x 1.6 ) x ( 1.25 - 0.25 x 5 )
=( 1,1 x 1,2 x1,3 x1,4 x1,5 x1,6 ) x ( 1,25 - 1,25 )
=( 1.1x1,2 x1,3 x1,4 x1,5 x1,6 ) x 0
=0
\(\dfrac{1}{1.4}+\dfrac{1}{4.7}+\dfrac{1}{7.10}+\dfrac{1}{10.13}+...+\dfrac{1}{x\left(x+3\right)}=\dfrac{34}{103}\)
\(\dfrac{1}{3}.\left(1-\dfrac{1}{4}+\dfrac{1}{4}-\dfrac{1}{7}+\dfrac{1}{7}-\dfrac{1}{10}+\dfrac{1}{10}-\dfrac{1}{13}+...+\dfrac{1}{x}-\dfrac{1}{x+3}\right)=\dfrac{34}{103}\)
\(\dfrac{1}{3}.\left(1-\dfrac{1}{x+3}\right)=\dfrac{34}{103}\)
\(1-\dfrac{1}{x+3}=\dfrac{34}{103}:\dfrac{1}{3}=\dfrac{34}{103}.3\)
\(1-\dfrac{1}{x+3}=\dfrac{102}{103}\)
\(\dfrac{1}{x+3}=1-\dfrac{102}{103}=\dfrac{103}{103}-\dfrac{102}{103}\)
\(\dfrac{1}{x+3}=\dfrac{1}{103}\)
\(\Rightarrow x+3=103\)
\(x=103-3\)
\(x=100\)
Vậy x = 100
\(\dfrac{6}{11}.\dfrac{3}{7}+\dfrac{3}{7}.\dfrac{5}{11}\)
\(=\dfrac{3}{7}.\left(\dfrac{6}{11}+\dfrac{5}{11}\right)\)
\(=\dfrac{3}{7}.1=\dfrac{3}{7}\)
1,4+X+X=15
1,4+X+Xx1=15
{1,4+1}xX=15
2,4xX=15
X=15:2,4
X=6,25
\(4+2x=15\Leftrightarrow2x=15-4\Leftrightarrow2x=11\Leftrightarrow x=\frac{11}{2}\)